2 keV filters of quasi-mono-energetic neutrons - M. Adib; N. Habib; I. I. Bashter; M. Fathallah; M. S. El-Mesiry; A. Saleh (Ядерна фізика та енергетика)
A simulation study for the production of 2 keV filters of quasi-mono-energetic neutrons based on the deep interference minima in the 45Sc total cross-section was carried out. A computer code QMENF-II was adapted to calculate the optimum amounts of the 45Sc as a main filter element and additional component ones to obtain sufficient intensity at high resolution and purity of the filtered quasi-mono-energetic neutrons. The emitted neutron spectrum from nuclear reactor and from the reaction of 2.6 MeV protons on a lithium fluoride target at the accelerator beam port, are used for simulation.